E-Atlas of Epidermal and Stomatal Anatomical Structures in Bougainvillea spp. as an Educational Media for Plant Anatomy - Claudia Jenatris Sendang; Getrudis Wilhelmina Nau (Al Jahiz, 2025)
The plant anatomy course studies the internal structures of plant organs, which cannot be observed directly, making it a challenging subject for students. Currently, no instructional media presents direct observation images of the epidermis and stomata of bougainvillea plants, which hinders students’ conceptual understanding. This study aims to develop a plant anatomy e-atlas focusing on the epidermis and stomata structures of bougainvillea (Bougainvillea spp.) as an instructional medium, and to evaluate its feasibility. The anatomical structures of the epidermis and stomata were identified from observations of eight bougainvillea varieties found at Widya Mandira Catholic University in Kupang. This research employed a Research and Development (R&D) method using the ADDIE model. The study began with an analysis of the epidermis and stomata structures using the replica method. The results were presented as images and then designed into an atlas format. The feasibility of the e-atlas was evaluated through expert validation. The findings revealed that: (1) The epidermal structure of bougainvillea leaves varies, with some varieties showing elongated and irregular shapes, while others exhibit pentagonal or hexagonal shapes; (2) Five types of stomata were identified: anomocytic, diacytic, paracytic, actinocytic, and anisocytic; (3) The validation results from the content expert and media expert were 84.44% and 83%, respectively, both falling into the 'highly valid' category. In conclusion, although all bougainvillea varieties belong to the same genus, they exhibit diverse epidermal and stomatal structures, and the developed e-atlas is feasible for use as instructional media in plant anatomy courses for Biology Education students.